The Relationship between Teachers' Perceptions of Organizational Justice and Authentic Leadership and Their Levels of Organizational Happiness - Demir, Hatice; Zincirli, Muhammed (İdeal Kent Yayınları, 2021)
The purpose of this study is to determine the relationship between teachers' perceptions of organizational justice and authentic leadership and their organizational happiness levels. The research was carried out in survey model. The population of the study consists of teachers working in public schools in Elazig province center in the 2019-2020 academic year. The sample of the research was determined by quota sampling method, and the research was carried out by analyzing the data obtained from 436 teachers serving at various grades. Within the scope of the research, the data were collected with the Organizational Justice Scale (OJS), the Authentic Leadership Scale (ALS), the Organizational Happiness Scale (OHS) and the personal information form prepared by the researcher. The data obtained were analyzed with reliability, percentage, frequencies, t-test, Pearson Correlation Analysis and Multiple Regression Analysis. According to the findings obtained from the study, it was observed that teachers' organizational justice, authentic leadership and organizational happiness scores did not differ significantly according to their gender and marital status. According to the results of Pearson correlation analysis, there are positive and significant relationships between the organizational justice and authentic leadership perceptions of the participants and their organizational happiness levels. Finally, because of the multiple regression analysis, it was determined that the participants' perceptions of organizational justice and authentic leadership (relational transparency sub-dimension) significantly predicted their organizational happiness levels, and these two variables explained approximately 18% of the change in organizational happiness. According to these results, it can be said that organizational justice and authentic leadership behaviors play a role in teachers' organizational happiness levels.

Bu çalışmanın amacı; öğretmenlerin örgütsel adalet ve otantik liderlik algıları ile örgütsel mutluluk düzeyleri arasındaki ilişkiyi tespit etmektir. Araştırmada tarama modeli kullanılmıştır. Çalışmanın evrenini, 2019-2020 Eğitim Öğretim yılında Elazığ il merkezindeki resmi okullarda görev yapan öğretmenler oluşturmaktadır. Araştırmanın örneklemi kota örnekleme yöntemiyle belirlenmiş olup, araştırma çeşitli kademelerde görev yapan 436 öğretmenden alınan verilerin analizi yapılarak gerçekleştirilmiştir. Araştırma kapsamında veriler, Örgütsel Adalet Ölçeği (ÖAÖ), Otantik Liderlik Ölçeği (OLÖ), Örgütsel Mutluluk Ölçeği (ÖMÖ) ve araştırmacı tarafından hazırlanan kişisel bilgi formu ile toplanmıştır. Elde edilen veriler, güvenirlik, yüzde, frekanslar, t-testi, Pearson Korelasyon analizi ve Çoklu Regresyon Analizine tutulmuştur. Araştırmadan elde edilen bulgulara göre, öğretmenlerin örgütsel adalet, otantik liderlik ve örgütsel mutluluk puanları, cinsiyet ve medeni durum değişkenleri açısından anlamlı düzeyde farklılaşmamaktadır. Katılımcıların örgütsel adalet ve otantik liderlik algıları ile örgütsel mutluluk düzeyleri arasında pozitif yönde anlamlı ilişkiler vardır. Katılımcıların örgütsel adalet ve otantik liderlik (ilişkilerde şeffaflık alt boyutu) algıları örgütsel mutluluk düzeylerini anlamlı şekilde yordamakta ve bu iki değişken örgütsel mutluluktaki toplam değişimin yaklaşık %18’ini açıklamaktadır. Bu bulgulara göre öğretmenlerin örgütsel mutluluk düzeylerinde örgütsel adaletin ve otantik liderlik davranışlarının rolü olduğu söylenebilir.
Öğretmenlerin Örgütsel Adalet ve Otantik Liderlik Algıları ile Örgütsel Mutluluk Düzeyleri Arasındaki İlişki
Keywords: Other Fields of Education; Alan Eğitimleri